2014
DOI: 10.1002/cpp.1895
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Associations Between Treatment for Anorexia Nervosa and Carers' Distress

Abstract: Only 61% of adults being treated for anorexia nervosa (AN) were willing to allow their carer to be contacted by researchers in order to ask them to complete questionnaires over the duration of treatment and follow-up. Significant reductions in eating psychopathology from those being treated for AN was followed by significant reductions in their carers' distress some 12 months later. Reductions of carers' distress was associated with only a small effect size and may indicate that more clinically significant red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…However, in a recent study, investigators specifically examined whether improvements in family outcomes were correlated with a reduction in eating disorder symptoms in individuals with AN (Slater et al, 2014). It is possible that the improvements in family outcomes may be related to the decreases in eating psychopathology and increase in BMI in the affected individual rather than the family based interventions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in a recent study, investigators specifically examined whether improvements in family outcomes were correlated with a reduction in eating disorder symptoms in individuals with AN (Slater et al, 2014). It is possible that the improvements in family outcomes may be related to the decreases in eating psychopathology and increase in BMI in the affected individual rather than the family based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the improvements in family outcomes may be related to the decreases in eating psychopathology and increase in BMI in the affected individual rather than the family based interventions. However, in a recent study, investigators specifically examined whether improvements in family outcomes were correlated with a reduction in eating disorder symptoms in individuals with AN (Slater et al, 2014). The results showed that decreases in psychological distress only occurred 3 months after the completion of treatment for the affected individual (Slater et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations